Arab Spring: Gejolak Revolusi yang serentak terjadi di Tunisia, Mesir dan Libya tahun 2010-2011 - Rauf, Hanan Muhamad (Universitas Pendidikan Indonesia dan APPS (Asosiasi Pendidik dan Peneliti Sejarah), 2023)
The main problems examined in this article are the simultaneous upheavals of the revolution in the North African States of 2010-2011. The method used is historical, using four steps of historical research: heuristics, source criticism, interpretation, and historiography. Based upon the research, it was found that the people of the North African region have never felt the freedom or democratic system that they have desired for so long. The dictatorship leadership caused the state to experience social, political, and economic gaps. The revolution’s driving forces are the people’s power, economic problems, and social media. The efforts carried out by the people include conducting demonstrations, which are assisted by the development of social media and the military. The government responded with anti-criticism and blocked social media and internet access. The impact of the revolution is the democratic system that every North African and Middle Eastern country wants to implement, which is affected by the domino effect of the Arab Spring revolution and the economic impact that has shaken not only the country but the surrounding countries and the international world. The Arab Spring Revolution, led by the popular movement, overthrew dictatorial leaders, including Ben Ali, Hosni Mubarak, and Muammar Khaddafi.